Portable and rapid arsenic speciation in synthetic and natural waters by an As(V)-selective chemisorbent, validated against anodic stripping voltammetry. (15th May 2020) - Bullen, Jay C.; Torres-Huerta, Aaron; Salaün, Pascal; Watson, Jonathan S.; Majumdar, Swachchha; Vilar, Ramon; Weiss, Dominik J.
Abstract: Inorganic arsenic speciation, i.e. the differentiation between arsenite and arsenate, is an important step for any program aiming to address the global issue of arsenic contaminated groundwater, whether for monitoring purposes or the development of new water treatment regimes. Reliable speciation by easy-to-use, portable and cost-effective analytical techniques is still challenging for both synthetic and natural waters. Here we demonstrate the first application of an As(V)-selective chemisorbent material for simple and portable speciation of arsenic using handheld syringes, enabling high sample throughput with minimal set-up costs. We first show that ImpAs efficiently removes As(V) from a variety of synthetic groundwaters with a single treatment, whilst As(III) is not retained. We then exemplify the potential of ImpAs for simple and fast speciation by determining rate constants for the photooxidation of As(III) in the presence of a TiO2 photocatalyst. Finally, we successfully speciate natural waters spiked with a mix of As(III) and As(V) in both Indian and UK groundwaters with less than 5 mg L −1 dissolved iron. Experimental results using ImpAs agreed with anodic stripping voltammetry (ASV), a benchmark portable technique, with analysis conditions optimised here for the groundwaters of South Asia. This new analytical tool is simple, portable and fast, and should find applications within the overall multi-disciplinary remediation effort that is taking place to tackle this worldwide arsenic problem. Graphical abstract: Image 1 Highlights: ImpAs chemisorbent material can speciate inorganic As(III) and As(V). ImpAs speciation successfully determined rate constants for oxidation of As(III). Rate constants obtained by ImpAs agree with electrochemistry (ASV). ImpAs successfully speciates oxic and anoxic ground waters with ≤5 mg L −1 Fe.